Unlocking Sustainable Performance in SMEs: The Interplay of Green AI Management, Pro-environmental Behaviour in the Tourism and Hospitality Sector: UK - Alharbi, Ahmad A.; Elshamly, Amina; Shawky, Nevien Mohammed Abdelkreem; Mahgoub, Ibrahim G. (Journal of Posthumanism, 2025)
In an era where sustainability is paramount, small and medium-sized enterprises (SMEs) in the UK's tourism and hospitality sector face a multifaceted challenge. This study investigates the interaction of variables essential for their sustainable performance, focusing on AI-Enhanced Green Management (AI-EGM). Drawing from the Resource-Based View and Social Exchange Theory, we propose that AI-Enhanced Green Management (AI-EGM) positively influences financial and environmental performance. Business Size moderates the relationship between AI-Enhanced Green Management (AI-EGM) and Sustainable Performance, acknowledging the diversity within the SME landscape. The empirical results underscore the significance of AI integration, firm characteristics, and a comprehensive sustainability framework in shaping the sustainability landscape for SMEs in the tourism and hospitality sector. These findings offer valuable insights for SMEs and contribute to the broader goal of global and local sustainability.